LEMBAGA PERLINDUNGAN SAKSI DAN KORBAN SEBAGAI GARDA TERDEPAN MELINDUNGI SAKSI DAN KORBAN DALAM MENJAMIN KEAMANAN DAN KEADILAN - Andi Muhammad Rusdi (Constitutum: Jurnal Ilmiah Hukum, 2025)
Indonesia, as a nation governed by law, has a constitutional obligation to guarantee protection and justice for all its citizens, including witnesses and victims of crime. In practice, these individuals often face threats, intimidation, and even violence, which hinders the upholding of justice. The existence of the LPSK (Lembaga Penita Masyarakat Indonesia/LPSK) is a crucial pillar for the continuity of a fair legal process and supports victims and witnesses who are vulnerable to threats, intimidation, or violence during the law enforcement process. This study discusses three issues: the LPSK's strategic role as a protector of witnesses and victims, the forms of protection provided by the LPSK, and challenges and solutions that can improve the LPSK's effectiveness. The research method used is normative juridical, based on secondary data derived from legislation, legal literature, and previous research. The research findings reveal that the LPSK plays a crucial role in supporting restorative justice and human rights protection. However, the LPSK still faces significant structural and operational challenges, including budget and human resource limitations, low public awareness, weak inter-agency coordination, and threats to protected individuals and LPSK personnel. Proposed solutions include strengthening regulations, increasing budgets and staffing, institutional synergy, and digitizing services to reach remote areas. With structural and cultural strengthening, the LPSK can function more optimally as a guardian of the rights of witnesses and victims and strengthen public trust in the Indonesian criminal justice system.